Vibrational study of caffeic acid phenethyl ester, a potential anticancer agent, by infrared, Raman, and NMR spectroscopy - Raschi, Ana Beatriz; Romano, Elida; Castillo, María Victoria; Leyton, Patricio; Paipa, Carolina; Maldonado, Luis Maria; Brandan, Silvia Antonia (2018)
The structural and vibrational properties of caffeic acid phenethyl ester (CAPE) were studied using infrared and Raman spectroscopy in the solid phase and multidimensional nuclear magnetic resonance (NMR) spectroscopy in solution. The theoretical structures of the compound and of its dimer in the gas phase and in DMSO solution by using density functional theory (DFT) were studied. The harmonic vibrational frequencies for the optimized geometry of CAPE and its dimeric species were calculated at the B3LYP level of theory using the 6–31G* basis set. These data allow a complete assignment of the vibration modes of the FTIR and Raman spectra in the solid state using the scaled quantum mechanical force field (SQMFF) methodology. The vibrational analysis for the dimer was performed taking into account the correlation diagram by means of the factor group analysis in accordance with the experimental structure determined by X-ray diffraction. The presence of the dimer of CAPE is supported by the IR bands at 1654, 1635, 1563, 1533, 1300, 1107, 1050, 738 cm−1 and the Raman bands at 1684, 1681, 1634, 1112, 1050, 928, 873, 850, 740, 445, 371 and 141 cm−1. The calculated 1H and 13C chemicals shifts are consistent with the corresponding experimental NMR spectra of the compound in solution. In addition, a natural bond orbital (NBO) study revealed the characteristics of the electronic delocalization of the stable structure, while the corresponding topological properties of the electronic charge density were analyzed by employing Bader's atoms in the molecules theory (AIM).